THE RELATIONSHIP OF ENVIRONMENTAL FACTORS AND THE EXISTENCE OF LARGER WITH THE EVENT OF Dengue Hemorrhagic Fever (DHF) IN PASURUAN REGENCY - Fajrina Hidayati; Fitria Eka Putri; Hubaybah; Andree Aulia Rahmat; Yudhastuti; Chatarina (Pusat Riset dan Inovasi Nasional, 2022)
Dengue Hemorrhagic Fever (DHF) is an acute viral-febrile disease, often characterized by headache, bone or joint pain and muscle, and rash as a symptom. In Indonesia in 2011 there were 65,432 cases with 595 deaths. East Java Province has determined outbreaks of DHF since 2015 in 37 districts / cities, with a total of 3,136 cases of dengue fever and 52 deaths. Pasuruan Regency is one of Kabupeten in East Java with the highest death rate from DHF compared to other regencies or cities, which is 28 people in 2020. There are many factors that can affect, pray the only environment and vector. The purpose of this research is to see the relationship of environmental factors and vector with the incidence of DBD in Pasuruan Regency. This research is an observational research with case control design. The sample in this research were 76 respondents consisting of 38 case groups and 38 control groups representing from 3 sub-districts in Pasuruan Regency (Gempol, Beji and Kraton Sub-district). Data analysis with Chi-Square test. The results showed that there was a relationship between water pH in house (p = 0.005, OR = 5,343), indoor air temperature (p = 0.046, OR = 3,221), air humidity in house (p = 0.049, OR = 3,923) and presence of larvae (p = 0.037, OR = 3.032) with the incidence of DHF in Pasuruan Regency. The most influential factor in increasing the risk of DHF incidence in Pasuruan Regency is the pH of water, the temperature inside the house and the presence of larvae around the house. It needs cross-sector cooperation to pay attention to the condition of environmental sanitation so it will not be a good place for Ae mosquito development. aegypti. Providing counseling to people who focus on the source of the problem, and the community in order to prevent the occurrence of transmission of DHF by breaking the chain of transmission.